desilya - Cañete, Jo Antonette Molina
Coming back home after thirteen years, a 16 year old is forced to remember what little she knows of home when her mother decides to run away. In a grueling road trip with her estranged grandmother, in a place that she has long forgotten, she soon realizes that she is not the only one looking for a mother. With one foot in the present and the other in the past, the three end up understanding that moving forward entails both feet and all six — together.